Viewpoint: spinocerebellar ataxias as diseases of Purkinje cell dysfunction rather than Purkinje cell loss - Kapfhammer, Josef P.; Shimobayashi, Etsuko (Frontiers in Molecular Neuroscience, 2023)
Spinocerebellar ataxias (SCAs) are a group of hereditary neurodegenerative diseases mostly affecting cerebellar Purkinje cells caused by a wide variety of different mutations. One subtype is caused by mutations of Protein Kinase C gamma (PKCγ), the dominant PKC isoform present in Purkinje cells. Mutations in the pathway in which PKCγ is active, i.e. in the regulation of calcium levels and calcium signaling in Purkinje cells, are the cause of several other variants of SCA. In SCA14, many of the observed mutations in the PKCγ gene were shown to increase the basal activity of PKCγ, raising the possibility that increased activity of PKCγ might be the cause of most forms of SCA14 and might also be involved in the pathogenesis of SCA in related subtypes. In this viewpoint and review article we will discuss the evidence for and against such a major role of PKCγ basal activity and will suggest a hypothesis of how PKCγ activity and the calcium signalling pathway may be involved in the pathogenesis of SCAs despite the different and sometimes opposing effects of mutations affecting these pathways. We will then widen the scope and propose a concept of SCA pathogenesis which is not primarily driven by cell death and loss of Purkinje cells but rather by dysfunction of Purkinje cells which are still present and alive in the cerebellum.